Practical actions for applied systematic conservation planning. Issue 6 (4th June 2019) - Botts, Emily A.; Pence, Genevieve; Holness, Stephen; Sink, Kerry; Skowno, Andrew; Driver, Amanda; Harris, Linda R.; Desmet, Philip; Escott, Boyd; Lötter, Mervyn; Nel, Jeanne; Smith, Tammy; et al.
Abstract: Systematic conservation planning is intended to inform spatially explicit decision making. Doing so requires that it be integrated into complex regulatory and governance processes, and there are limited instances where this has been achieved effectively. South Africa is a global leader in the application of conservation plans, the outputs of which are widely used for spatial planning and decision making in many spheres of government. We aimed to determine how conservation planning in the country progressed from theory to implementation, and to identify practical actions that enabled this transition, by assessing temporal trends in the characteristics of conservation plans (1990–2017, n = 94). Since 2010 conservation planning has entered an operational period characterized by government leadership of plans, administrative rather than ecological planning domains, decreasing size of planning units, increasing emphasis on end‐user products, and scheduled revision of plans. Key actions that enabled this progression include transitioning leadership of plans from scientists to practitioners, building capacity within implementing agencies, creating opportunities to integrate plans in legislative processes, establishing a strong community of practice, adopting implementation‐focused methods, and balancing standardization with innovation. Learning from this model will allow other countries, particularly those with a similar megadiverse, developing context, to operationalize conservation planning into spatial planning and decision making. Abstract : Article impact statement : Systematic conservation planning can be operationalized into government policy and regulatory processes. Abstract : Acciones Prácticas para la Aplicación de la Planeación Sistemática de la Conservación Resumen: La intención de la planeación sistemática de la conservación es informar la toma de decisiones espacialmente explícitas. Para lograr esto se requiere la integración de la planeación sistemática dentro de los complejos procesos regulatorios y de gobernanza. Actualmente existen instancias limitadas en las que lo anterior se ha conseguido de manera efectiva. Sudáfrica es un líder mundial en la aplicación de planes de conservación, cuyos resultados se utilizan ampliamente para la planeación espacial y la toma de decisiones en muchas esferas del gobierno. Buscamos determinar cómo la planeación de la conservación ha progresado en este país desde la teoría hasta la implementación e identificar las acciones prácticas que permitieron esta transición, esto mediante la evaluación de tendencias temporales en las características de los planes de conservación (1990‐2017, n = 94). Desde 2010 la planeación de la conservación ha entrado en un periodo operativo caracterizado por el liderazgo gubernamental de los planes, dominios administrativos en lugar de dominios ecológicos, la reducción del tamaño de las unidades de planeación, el incremento del énfasis sobre los productos de usuario final y una revisión programada de los planes. Las acciones clave que permitieron esta progresión incluyen la transición del liderazgo de los planes de los científicos hacia los practicantes, el desarrollo de capacidades dentro de las agencias implementadoras, la creación de oportunidades para integrar los planes dentro de los procesos legislativos, el establecimiento de una comunidad de práctica fuerte, la adopción de métodos enfocados en la implementación y el balance entre la estandarización y la innovación. El aprendizaje que proporciona este modelo permitirá que otros países, particularmente aquellos con un contexto similar en cuanto al desarrollo y a la megadviversidad, conduzcan la planeación de la conservación hacia la planeación y la toma de decisiones espacialmente explícitas.